Description of the Historical and Current South Florida Recreational Tournament Fishery for Swordfish, Xiphias gladius - Brewer, Elaine J.; Kerstetter, David W. (NSUWorks, 2010)
Swordfish (Xiphias gladius) are increasingly sought after by recreational anglers around the world. The Florida Straits in particular are an important breeding and nursery area for North Atlantic swordfish, as well as being historical fishing grounds for both recreational and commercial swordfish fisheries. Despite the recreational fishing popularity of the species, there is no comprehensive description of the recreational fishery for swordfish. In the absence of a well monitored fishery, organized tournaments may provide a standardized set of fisheries‐dependent data with which to generate a description of both the historic (1977‐1983) and current (2000‐present) fisheries. Data were obtained from tournament websites, magazine articles, and personal communications with tournament directors and local fisheries researchers. To date, information has been gathered from 88 swordfish (16 historic, 72 current) and 118 istiophorid billfish tournaments (all from the current period) that occurred on the east coast of Florida between Stuart and Key West, the region with the vast majority of U.S. swordfish tournaments. The current trend of boat participation shows a strong correlation with catches over time in both the historic and current periods. Although the participation correlates to the number of catches, catch per hour (CPH) remains on a slow although not significant decrease over time. This comes as a surprise as swordfish anglers state the species is an increasingly more difficult one to target, suggesting that this decrease should be occurring at a more rapid rate. The median entry fee for these current period swordfish tournaments is between 200 and 600 dollars while those for billfish tournaments are tenfold the swordfish entry costs. In conjunction with this, the awarded prize monies of billfish tournaments are tenfold of the awarded prize monies for swordfish tournaments, and are shown to be significantly different (F = 18.75, p << 0.001). Despite the steady recent decrease of catches in tournaments, swordfish remain a popular target for anglers in south Florida. With constant monitoring and evaluations, the south Florida recreational tournament fishery for swordfish may provide a pivotal baseline to compare swordfish recreational fisheries in other areas to increase management knowledge of the fishery as a whole.